The future of warfare in the 21st century (The Emirates Center for Strategic Studies and Research, 2014)
The ECSSR 18th Annual Conference, The Future of Warfare in the 21st Century, held at the Center on April 9-10, 2013 in Abu Dhabi, and the resultant papers contained in this volume, explore how warfare may be affected by technological, strategic and civil developments in the coming years, particularly the revolutionary.